Hans Jonas : the integrity of thinking - Levy, David J. (Eric Voegelin Institute series in political philosophy., 2002)
"Hans Jonas: The Integrity of Thinking provides the first overall account of the work of Hans Jonas. While Jonas is not the best-known thinker of the twentieth century, David J. Levy shows that he is one of the most important. Levy covers the philosopher's life and his contributions to the history of religion, philosophical biology, philosophical anthropology, ethics, and theology. Jonas's work is situated in relationship to that of his first intellectual mentor, Martin Heidegger, as well as that of such related thinkers among his contemporaries as Eric Voegelin." "Setting Jonas's work in the historical and philosophical context of his life and times, Levy summarizes Jonas's original achievements in fields as apparently diverse as the history of ancient Gnosticism, the philosophical significance of biology, the problems of ethics in a technological age, and the mysteries of theology, while demonstrating the notable unity of theme and purpose that guided his various fields of inquiry." "Unlike the scattered works, anthologies, and essays that are currently available, Hans Jonas: The Integrity of Thinking provides a much-needed single, coherent overview of the various fields to which Jonas's attention was drawn, bringing out the unified, systematic quality of Jonas's philosophical approach."--Jacket